1242. Hepatitis C Treatment as a Complement to Syringe Service Programs: Pilot Progress and Pathways Forward. (15th December 2022) - Guzman, Miriam; Smith, Renata; Mayer, Stockton; Messmer, Sarah; Huyck, Michael; Cotler, Karen F; Chaisson, Lelia H; Jimenez, Antonio; Guerrero, Stephanie; Fortson, Neisha; Tai, Rex
Abstract: Background: Hepatitis C (HCV) poses a significant chronic infectious disease threat in the United States, and people who inject drugs (PWID) are at elevated HCV risk. We assessed implementation of a program that provided low-barrier services for high-risk PWID, coupling harm reduction with clinical care, including HCV treatment. Methods: In 2018, the University of Illinois at Chicago established a program to deliver comprehensive care to PWID in an underserved Chicago neighborhood, including syringe services (SS) and HCV treatment. We performed chart reviews of SS clients who sought HCV care from 09/2018-01/2021. We assessed patient demographics; the proportions prescribed and initiated on HCV treatment; and the proportions with undetectable HCV RNA at treatment week 4, end of treatment, and 12-weeks post-treatment. Results: Among 67 patients, 45 (67%) were male, median age was 45 years (IQR 35-57), 22 (33%) were Black, and 11 (16%) were Hispanic. 66 (99%) reported current or former drug use and 62 (93%) injection drug use, and 3 (4%) sex work. 36 (54%) were undomiciled or lived in unstable housing, 22 (33%) were unemployed, 19 (28%) had been incarcerated within the past year, and 30 (45%) had a history of psychiatric illness. Median pre-treatment HCV RNA was 701, 626 IU/L (IQR 39, 944-1, 979, 898). 40 (60%) were prescribed HCV treatment and 31 (46%) initiated treatment (Figure ). Of these, 21/31 (68%) completed HCV RNA testing at treatment week 4, of whom 18/21 (86%) had an undetectable viral load; 16/31 (52%) completed end of treatment testing, of whom 16/16 (100%) had an undetectable viral load; and 15/31 (48%) completed 12-week post-treatment testing, of whom 13/15 (87%) had an undetectable viral load. Of the 2 patients who did not achieve sustained viral suppression following treatment, 1 missed four weeks of treatment due to incarceration and 1 reported full adherence to treatment. Numbers and percentages of patients at each step in the treatment cascade Conclusion: This comprehensive program offering SS and HCV care successfully reached PWID in an underserved area before and during the pandemic. Losses along the HCV treatment cascade were high: Only 60% were prescribed treatment and less than one-third of those prescribed treatment achieved sustained viral suppression. Among those who remained in care, over 80% achieved sustained viral suppression. Disclosures: All Authors : No reported disclosures.